G-induced loss of consciousness for fighter pilots - Foo, Jonathan Zhi Bao. (2009)
The goal of this project is to further the study of Gravity induced Loss of Consciousness in Fighter Pilots. G induced loss of consciousness or G-LOC is defined in aviation medicine as “a state of altered perception whereby one’s awareness of reality is absent due to a sudden, critical reduction of cerebral blood circulation caused by an increase in G force”. The G-LOC phenomenon is not a single event but a complicated series of events. It involves loss of vision, loss of other sensory input, loss of motor output, loss of memory and loss of consciousness subsequently followed by recovery of these faculties. As G-LOC is one of the main factors contributing to aviation accidents resulting in loss of pilot lives and aircraft worth millions of dollars, there is a strong interest in this research. Furthermore, with the advancements in aviation technology resulting in aircrafts with a higher speed performance and ability to operate in higher pressure altitude condition, there is increased urgency in the study of G-LOC. The model created in this project was a modification of the Windkessel theory. It is an electric circuit analogy of the circulatory system, with parameters and elements to simulate the physiological responses of the human body when subjected to increasing G-loading. The input was a human’s aortic pressure waveform reconstructed from the first 10 harmonics using fourier series. 6 models with different parameters were created. Model 1 varies fluid resistance of the cerebral circulation with +Gz while Model 2 varies abdominal resistance to varying +Gz. Model 3 is the combination of Model 1 and 2. Model 4 and 5 are variations on the abdominal resistance to G-loading. Model 6 includes the baroreflex mechanism from the activation of baroreceptors for complete analysis under G-loading, predicting critical values of A-LOC, G-LOC and cell death occurring at 3.3G, 5G and 9G respectively. Using data from Model 6, the relationship between cerebral blood flow and the G-load factor could be established.